Who's Afraid of the Vienna Sales Convention (CISG)? A New Zealanders View from Australia and Japan - Nottage, Luke (Victoria University of Wellington Law Review, 2005)
Luke Nottage first sets out the structure of the CISG by reference to a New Zealand – Japan sales dispute. He prefers the CISG over traditional Anglo-Commonwealth law rules and then examines why lawyers and academics have not necessarily embraced the CISG, drawing partly on lessons from behavioural law and economics. He concludes with a call to action by those involved in the practice and study of international sales law.